Structural, optical and electrical properties of sol-gel derived titanium dioxide thin film - (:unkn) unknown (My University, 2007)
Optical, structural and electrical (dc and ac) properties of sol-gel derived TiO 2 film in a wide range of temperature (290 - 652 K) were investigated. XRD analysis was used for investigation the crystallinity of the films. Optical bad gap of the film were determined from transmission spectra. With the examination of the impedance spectra clear differences could be seen in the dependence of ω on both real and imaginary part of impedance between 290 K and 652 K. The impedance response is significantly changed with the increase of temperature. © 2007 American Institute of Physics.
Keywords: Anatase; Impedance spectroscopy; Sol-gel; XRD